EFFECT OF ISO 9001:2015, ISO 14001:2015 AND ISO 45001:2018 ON OPERATIONAL PERFORMANCE OF AUTOMOTIVE INDUSTRIES - Fahmi, Khaerul; Mustofa, Ali; Rochmad, Imbuh; Sulastri, Eva; Wahyuni, Indah Sri; Irwansyah, Irwansyah (Journal of Industrial Engineering & Management Research, 2021)
The purpose of this study was to analyze the effect of implementation ISO 9001: 2015 quality management system, ISO 45001: 2018 occupational safety management system on operational performance. The method used in this study is a quantitative method and data processed by structural equation modeling (SEM) using SmartPLS 3.0 software. Data collection by distributing questionnaires online to 220 managers in automotive industries in Indonesia who have implemented ISO 9001, ISO 14001 and ISO 45001 Questionnaire forms were distributed online and the sampling method using snowball sampling. The results of this study are the application of ISO 9001: 2015 quality management system has a positive and significant relationship to manufacturing performance, the application of ISO 14001: 2015 environmental management system has a positive and significant relationship to operational performance, the application of work safety management system ISO 45001: 2018 has a relationship positive and significant impact on operational performance in automotive industries.